Public relations for Asia. - Morris, Trevor, ....-; Goldsworthy, Simon, ....- (Hampshire : Palgrave, 2008)
This book is an essential read for anyone interested in Public Relations in Asia. Whether you are working in PR, studying PR, a journalist dealing with PR, or just interested in this fascinating and fast growing market, Public Relations in Asia offers readers a vital insight into how PR works. Combining the latest in Public Relations theory with clear and practical guidance on how to plan and structure a PR campaign, as well as invaluable top tips on the skills needed to create successful PR campaigns, Public Relations in Asia is also full of fascinating and relevant case histories from around Asia and the rest of the world.
Keywords: Public relations